Assessing the Durability of Concrete with the Addition of Low Quality Fly Ash - Ali Ajwad; Usman Ilyas; Nouman Khadim; Abdullah; Muhammad Usman; Shakir Ahmad; Bilal Zahid; Abdul Waqar Akhtar (Scientific Inquiry and Review, 2019)
The life span of a structure is basically determined by its durability. Over the course of time, concrete carbonation and corrosion of steel reinforcement lead to weakness in concrete’s structural elements and hence reduce its useful life. The addition of fibers in concrete can act as barrier and delays the activation of these processes. In this study, low quality fly ash was added to concrete to check its effect on the durability of concrete. It was found that the addition of low quality fly ash with an activator does have a positive impact on carbonation and reinforcement of corrosion resistance.